2019
DOI: 10.1093/humrep/dez036
|View full text |Cite
|
Sign up to set email alerts
|

Moderate maternal folic acid supplementation ameliorates adverse embryonic and epigenetic outcomes associated with assisted reproduction in a mouse model

Abstract: Could clinically-relevant moderate and/or high dose maternal folic acid supplementation prevent aberrant developmental and epigenetic outcomes associated with assisted reproductive technologies (ART)?SUMMARY ANSWER: Our results demonstrate dose-dependent and sex-specific effects of folic acid supplementation in ART and provide evidence that moderate dose supplements may be optimal for both sexes.WHAT IS KNOWN ALREADY: Children conceived using ART are at an increased risk for growth and genomic imprinting disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 42 publications
(55 reference statements)
2
55
0
Order By: Relevance
“…In addition to placenta overgrowth, IVF placentas exhibit biallelic expression of imprinted genes, which are normally monoallelically expressed, concomitant with loss of allele-specific DNA methylation of their regulatory imprinting control regions (ICRs) (de Waal et al, 2014;de Waal et al, 2015;Rahimi et al, 2019;Whidden et al, 2016). To ascertain whether an association exists between these DNA methylation changes and the morphological phenotypes over the span of placenta development, we measured DNA methylation of the paternally methylated ICR H19/Igf2 and three maternally methylated ICRs -Kcnq1ot1, Peg3 and Snrpnby bisulfite pyrosequencing.…”
Section: Ivf Increases Sflt1 Levels a Protein Implicated In Causing mentioning
confidence: 99%
“…In addition to placenta overgrowth, IVF placentas exhibit biallelic expression of imprinted genes, which are normally monoallelically expressed, concomitant with loss of allele-specific DNA methylation of their regulatory imprinting control regions (ICRs) (de Waal et al, 2014;de Waal et al, 2015;Rahimi et al, 2019;Whidden et al, 2016). To ascertain whether an association exists between these DNA methylation changes and the morphological phenotypes over the span of placenta development, we measured DNA methylation of the paternally methylated ICR H19/Igf2 and three maternally methylated ICRs -Kcnq1ot1, Peg3 and Snrpnby bisulfite pyrosequencing.…”
Section: Ivf Increases Sflt1 Levels a Protein Implicated In Causing mentioning
confidence: 99%
“…Recent study examined the genome-wide DNA methylation patterns in placentas and embryos in correlation with maternal FA supplementation in the prevention of CAs associated with assisted reproductive technologies (ART). Results demonstrate dose-dependent and sex-specific effects of FA intake; moderate dose of FA supplements may be optimal in ART for both sexes [139]. Even more, recent data suggest that genome-wide DNA methylation in the placentas from preterm infants could be associated with maternal socioeconomic status [140].…”
Section: Epigenetic Pattern Transmission From Parent To Offspring: Unmentioning
confidence: 90%
“…In our study, we showed that FA supplementation (8 mg/kg) has reduced the effect of aging on oocyte aneuploidy by significantly increasing the proportion of normal oocytes in old female mice fed the supplemented FA diet for 24-week. Also, a similar level of FA supplementation (8 mg/kg) was shown to be beneficial for mice undergoing ART by reducing embryonic developmental delay and loss (Rahimi et al, 2019). It should be noted that the 8 mg FA/day supplementation is comparable to the combined FA intake from both fortified foods and over-the-counter prenatal supplements.…”
Section: Implications For Female Reproductive Healthmentioning
confidence: 84%
“…In mice, it has been reported recently that ART use was associated with increased embryonic loss and developmental delay (Rahimi et al, 2019). A high incidence of aneuploidy has been reported in the abortuses of infertile patients who conceived pregnancy using ART (Lathi & Milki, 2004;Nayak et al, 2011) and this high incidence of aneuploidy was associated with advance maternal age (Kushnir & Frattarelli, 2009;Spandorfer et al, 2004).…”
Section: Implications For Female Reproductive Healthmentioning
confidence: 98%
See 1 more Smart Citation